Linking Antimicrobial Resistance Surveillance Data to Provincial Hospital Records: A Descriptive Study of Patient and Facility-level Characteristics. (2018) - Lee, Seungwon; Ronksley, Paul E; Garies, Stephanie; Quan, Hude; Faris, Peter; Li, Bing; Henderson, Elizabeth
No abstract available